Dinámica espacio - temporal de la pesquería artesanal de “boquichico”, Prochilodus nigricans (Spix & Agassiz, 1829) (characiformes: prochilodontidae) mediante la base de datos de la DIREPRO (2011 - 2021) en el departamento de Loreto - Tapullima Vásquez, Sol Norhelia (2023)
The objective of this work was to analyze the spatio-temporal dynamics of the artisanal fishery of Prochilodus nigricans "BOQUICHICO", through the use of the DIREPRO database - period 2011-2021, department of Loreto - Peru. For this, the statistical information of the fishing landing volumes that the DIREPRO manages in Loreto was used; data that allowed knowing the fishing production of Prochilodus nigricans through landing volumes, as well as the existence of significant differences in the spatio-temporal dynamics of the artisanal fishery of the species under study; The information was processed in the Microsoft Office Professional Plus 2016 Excel program. The results show that the landing volume of the species Prochilodus nigricans during this period of time was 29,112.30 ± 4,812.11 t, with Iquitos being the locality that registered the highest volume. landing (55.08%), followed by Yurimaguas with 18.93%; In relation to the state of conservation of the landing volumes, there is a record of 85.47% in the fresh state, 2.72% in the salty state, and 11.81% in the dry salty state, as well as the significance analysis of Kruskal-Wallis, evidences the absence of significant differences between the volume of fishing landings and the years of analysis, that is, the periods between 2011 and 2021. The work concludes that Iquitos is the locality that registers the highest volume of landings of Prochilodus nigricans; while the most representative state of conservation in the landing volumes is fresh.